Can Governance in Revenue Sharing Be a Pathway for a Win-win Situation between People’s Livelihood Improvement and Conservation? - Twinamatsiko, Medard; Rugunda, Grace Kagoro; Basheka, Benon; Herdt, Tom De (Journal of Social Science Research, 2015)
This paper establishes the importance of good governance in improving local livelihoods and support for conservation. The study uses empirical realities from Bwindi Impenetrable National Park, an afromontane Gorilla sanctuary that was recognized by UNESCO in 2005 as a world heritage due to its rich biodiversity. Governance is an important procedural dimension of equity that entails decision making processes and how local people are involved in matters that most affect them. The paper uses a Policy Arrangements Approach to illustrate the procedural dimension of the Justice and Equity Framework. A mixed method approach was used to generate results in this paper. Household surveys, key informant interviews and Focus Group Discussions were employed for data collection. Linear and Multinomial Logistic Regressions were used to determine the level of significance and relationships that exist between governance, people’s livelihoods and conservation support. Polychoric Principal Component Analysis (PCA) was used to generate indices of livelihood improvement and conservation support. Results revealed that meaningful involvement, leadership composition on committees, local capacity, information flow and awareness and accountability significantly influence people’s livelihoods and conservation of Bwindi. Local people are not only concerned about distributive equity in benefit sharing but also the procedural dimension. This entails being part of revenue sharing projects from the design phase to the evaluation phase. The study recommends the use of equity framework in revenue sharing in order to increase greater involvement of local people in decision making processes.
Keywords: Governance, Revenue Sharing Policy; Involvement; Procedural Equity; People’s Livelihood; Conservation support; Bwindi